Ocular involvment of coronavirus disease (COVID-19): A systematic review of conjunctival swab results - Indra Tri Mahayana; Natalia Christina Angsana; Muhammad Zhafran Ayyasy; Anastasya Sondang Hutajulu; Suhardjo Suhardjo (Journal of Community Empowerment for Health, 2020)
Coronavirus disease (COVID-19) is a pandemic disease which is caused by the latest discovered coronavirus. Conjunctivitis is allegedly the first presentation of COVID-19 since it can spread by aerosol contact with the conjunctiva. The present study aimed to systematically review the employment of conjunctival swab with Real-time Polymerase Chain Reaction in detecting SARS-Cov-2. The research is a systematic review of the published scientific literature on findings of conjunctival swab of COVID-19 from PUBMED database and other additional sources (i.e: Google Scholar). The search method was done using “COVID-19 OR coronavirus OR SARS-COV2, AND conjunctivitis, AND ocular manifestations, AND conjunctival swab” as keywords. Inclusion criteria were any papers that related to the entered keywords and have conjunctival swab as a reported outcome. Letters, reviews, and editorials describing other studies reporting COVID-19 and conjunctival swab were excluded. Only four research papers were found and included in the literature review. From the four current research papers, positive SARS-CoV-2 results were yielded from 0-5.26% of conjunctival swab specimens. In conclusion, although the presence of the SARS-CoV-2 virus on the ocular surface remains unclear, the prevention of infection transmission through an ocular surface is mandatory by wearing goggles (or shield), mask (N-95 recommended) and gown.